2018
DOI: 10.1016/j.jtbi.2018.04.030
|View full text |Cite
|
Sign up to set email alerts
|

A guideline to study the feasibility domain of multi-trophic and changing ecological communities

Abstract: The feasibility domain of an ecological community can be described by the set of environmental abiotic and biotic conditions under which all co-occurring and interacting species in a given site and time can have positive abundances. Mathematically, the feasibility domain corresponds to the parameter space compatible with positive (feasible) solutions at equilibrium for all the state variables in a system under a given model of population dynamics. Under specific dynamics, the existence of a feasible equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(158 citation statements)
references
References 40 publications
0
158
0
Order By: Relevance
“…This range of conditions (combination of intrinsic growth rates or carrying capacities) is called the feasibility domain D F (A) [26,36]. For example, heterotrophic species should exhibit smaller negative intrinsic growth rates than the benefits they can obtain from other species in order to have a positive balance of biomass (hence feasibility) [37,38]. This feasibility domain forms an algebraic cone [19,36]:…”
Section: Methods (A) Structural Stabilitymentioning
confidence: 99%
“…This range of conditions (combination of intrinsic growth rates or carrying capacities) is called the feasibility domain D F (A) [26,36]. For example, heterotrophic species should exhibit smaller negative intrinsic growth rates than the benefits they can obtain from other species in order to have a positive balance of biomass (hence feasibility) [37,38]. This feasibility domain forms an algebraic cone [19,36]:…”
Section: Methods (A) Structural Stabilitymentioning
confidence: 99%
“…Second, our results might be applicable only for the parameters tested in this study. Recent theoretical works showed that only a subspace of critical parameters (such as intrinsic growth rate) led to feasible equilibriums, namely, structural stability (Song et al 2018). The BCR networks were also subject to this limitation, and it is worthy for further exploration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This means that weak (less frequent) links between specialists were more vulnerable than strong (more frequent) links between generalists (8). Importance was defined as the contribution of a given link to the feasibility of a network, where feasibility is a measure of a network's ability to withstand environmental variation without leading to species extinctions (15,16). Important links were those that, when removed, lowered a network's feasibility; that is, when removed, they reduced the…”
Section: Relationship Between Link Vulnerability and Importancementioning
confidence: 99%
“…Feasibility is defined as the range of conditions under which all species in a community can stably coexist (16). Feasibility can therefore be thought of as the 'safe operating space' of ecological communities: it is an indicator of how much environmental stress a community can tolerate before extinction of any of its constituent species.…”
Section: Link Importancementioning
confidence: 99%
See 1 more Smart Citation